Towards Novel Geneless Approaches for Therapeutic Angiogenesis - Moccia, Francesco; Antognazza, Maria Rosa; Lodola, Francesco (Frontiers in Physiology, 2021)
Cardiovascular diseases are the leading cause of mortality worldwide. Such a widespread diffusion makes the conditions affecting the heart and blood vessels a primary medical and economic burden. It, therefore, becomes mandatory to identify effective treatments that can alleviate this global problem. Among the different solutions brought to the attention of the medical-scientific community, therapeutic angiogenesis is one of the most promising. However, this approach, which aims to treat cardiovascular diseases by generating new blood vessels in ischemic tissues, has so far led to inadequate results due to several issues. In this perspective, we will discuss cutting-edge approaches and future perspectives to alleviate the potentially lethal impact of cardiovascular diseases. We will focus on the consolidated role of resident endothelial progenitor cells, particularly endothelial colony forming cells, as suitable candidates for cell-based therapy demonstrating the importance of targeting intracellular Ca2+ signaling to boost their regenerative outcome. Moreover, we will elucidate the advantages of physical stimuli over traditional approaches. In particular, we will critically discuss recent results obtained by using optical stimulation, as a novel strategy to drive endothelial colony forming cells fate and its potential in the treatment of cardiovascular diseases.